Antimicrobial Activity, Genetic Relatedness, and Safety Assessment of Potential Probiotic Lactic Acid Bacteria Isolated from a Rearing Tank of Rotifers (Brachionus plicatilis) Used as Live Feed in Fish Larviculture - Contente, Diogo; Díaz Formoso, Lara; Feito Hermida, Javier; Gómez Sala, Beatriz; Costas, Damián; Hernández Cruza, Pablo Elpidio; Muñoz Atienza, Estefanía; Borrero Del Pino, Juan; Poeta, Patrícia; Cintas Izarra, Luis Miguel (Animals, 2024)
2024 Descuento MDPI Aquaculture is a rapidly expanding agri-food industry that faces substantial economic losses due to infectious disease outbreaks, such as bacterial infections. These outbreaks cause disruptions and high mortalities at various stages of the rearing process, especially in the larval stages. Probiotic bacteria are emerging as promising and sustainable alternative or complementary strategies to vaccination and the use of antibiotics in aquaculture. In this study, potential probiotic candidates for larviculture were isolated from a rotifer-rearing tank used as the first live feed for turbot larvae. Two Lacticaseibacillus paracasei and two Lactiplantibacillus plantarum isolates were selected for further characterization due to their wide and strong antimicrobial activity against several ichthyopathogens, both Gram-positive and Gram-negative. An extensive in vitro safety assessment of these four isolates revealed the absence of harmful traits, such as acquired antimicrobial resistance and other virulence factors (i.e., hemolytic and gelatinase activities, bile salt deconjugation, and mucin degradation, as well as PCR detection of biogenic amine production). Moreover, Enterobacterial Repetitive Intergenic Consensus-PCR (ERIC-PCR) analyses unveiled their genetic relatedness, revealing two divergent clusters within each species. To our knowledge, this work reports for the first time the isolation and characterization of Lactic Acid Bacteria (LAB) with potential use as probiotics in aquaculture from rotifer-rearing tanks, which have the potential to optimize turbot larviculture and to introduce novel microbial management approaches for a sustainable aquaculture. Ministerio de Ciencia, Innovación y Universidades (España) Fundação para a Ciência e a Tecnologia (Portugal) Comunidad de Madrid European Commission Ministerio de Trabajo y Economía Social (España) Depto. de Nutrición y Ciencia de los Alimentos Fac. de Veterinaria TRUE pub Descuento UCM